2020
DOI: 10.1007/s00423-020-01972-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of contemporary pancreas surgery with arterial resection

Abstract: Objective Advances in multimodality treatment paralleled increasing numbers of complex pancreatic procedures with major vascular resections. The aim of this meta-analysis was to evaluate the current outcomes of arterial resection (AR) in pancreatic surgery. Methods A systematic literature search was carried out from January 2011 until January 2020. MOOSE guidelines were followed. Predefined outcomes were morbidity, pancreatic fistula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
1
19
0
3
Order By: Relevance
“…Recent reports have documented favorable short-term outcomes of venous resection in patients with localized PCs [ 10 , 11 ]; however, the R0 resection rate, as well as long-term survival, remained unsatisfactory, because the most frequent site of cancer-positive margin was located at the superior mesenteric artery (SMA) margin [ 12 , 13 ], which could not be overcome by venous resection alone. Therefore, the necessity of more radical dissection, including arterial resection, remained and has become more prominent in the past two decades, although recent meta-analyses concluded that pancreatectomy with ARs remained a challenge, because it increased the complexity of the procedure and was associated with increased morbidity and mortality in comparison to non-AR pancreatectomies [ 14 , 15 ].…”
Section: Arterial Resectionsmentioning
confidence: 99%
“…Recent reports have documented favorable short-term outcomes of venous resection in patients with localized PCs [ 10 , 11 ]; however, the R0 resection rate, as well as long-term survival, remained unsatisfactory, because the most frequent site of cancer-positive margin was located at the superior mesenteric artery (SMA) margin [ 12 , 13 ], which could not be overcome by venous resection alone. Therefore, the necessity of more radical dissection, including arterial resection, remained and has become more prominent in the past two decades, although recent meta-analyses concluded that pancreatectomy with ARs remained a challenge, because it increased the complexity of the procedure and was associated with increased morbidity and mortality in comparison to non-AR pancreatectomies [ 14 , 15 ].…”
Section: Arterial Resectionsmentioning
confidence: 99%
“…A non‐tumour infiltrated plane is opened by blunt or sharp dissection and followed with a circumferential vascular dissection 7 . This approach allows avoiding arterial resection and reconstruction, which is associated with non‐negligible morbi‐mortality 8 in spite of no or limited survival advantage (in the setting of pancreatic carcinoma) 9 . The use of arterial divestment may have advantages over arterial resection also for pancreatic NETs.…”
Section: Figmentioning
confidence: 99%
“…The first evidence in the literature for the CA resection without reconstruction was reported for a case of gastric cancer requiring total gastrectomy by Appleby in 1953 [ 24 ]. Nowadays, arterial resection of the CA has been translated to DP, in a procedure named DP-CAR [ 25 , 26 ]. This technique has been debated over the years due to its technical difficulty and its morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%